2020
DOI: 10.1097/md.0000000000021498
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy-associated lipid changes in breast cancer patients

Abstract: Adjuvant chemotherapy may cause alterations in serum lipids in postoperative breast cancer (BC) patients, but the specific alterations caused by different chemotherapy regimens remain unclear. The aim of this study was to investigate the status of serum lipids pre- and post-chemotherapy and to compare the side effects of different chemotherapy regimens on serum lipid. We retrospectively analysed the lipid profiles of 1934 consecutive postoperative BC patients who received one of the following chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 48 publications
(44 reference statements)
2
22
0
Order By: Relevance
“…It was reported that cytotoxic drugs affect blood lipid metabolism differently [ 20 ]. Breast cancer patients often display increased total cholesterol, LDL-C, and TG levels during chemotherapy [ 15 18 ], while colorectal cancer patients treated with chemotherapy show increased HDL-C and decreased LDL-C [ 19 ]. However, it remains unclear whether lipid alterations exist in NSCLC patients receiving standard adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that cytotoxic drugs affect blood lipid metabolism differently [ 20 ]. Breast cancer patients often display increased total cholesterol, LDL-C, and TG levels during chemotherapy [ 15 18 ], while colorectal cancer patients treated with chemotherapy show increased HDL-C and decreased LDL-C [ 19 ]. However, it remains unclear whether lipid alterations exist in NSCLC patients receiving standard adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy agents can also affect lipid metabolism. A few studies assessed breast cancer patients who received chemotherapy, and discovered significantly increased total cholesterol, LDL-C, and TG levels [ 15 18 ]. In colorectal cancer patients, chemotherapy significantly increased HDL-C and decreased LDL-C [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…She and her family reported that her food intake was stable, suggesting that her lipid intake did not change. It has been reported that serum lipid levels, such as triglyceride, total cholesterol, and low-density lipoprotein, were significantly but not severely elevated after chemotherapy in breast cancer treatment [ 11 ]. He et al [ 11 ] speculated that chemotherapy itself can directly cause endothelial dysfunction and insulin resistance, leading to cytokine alterations, resulting in elevated serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that serum lipid levels, such as triglyceride, total cholesterol, and low-density lipoprotein, were significantly but not severely elevated after chemotherapy in breast cancer treatment [ 11 ]. He et al [ 11 ] speculated that chemotherapy itself can directly cause endothelial dysfunction and insulin resistance, leading to cytokine alterations, resulting in elevated serum lipid levels. They also proposed another possibility that suggests that the enhancement of systemic oxidative stress causes lipid peroxidation, leading to liver dysfunction, and resulting in a decrease in lipid metabolism [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation